Vaksinasi Terhadap Motivasi Belajar Anak Usia Sekolah - Erita, Erita; Rezkiki, Fitrianola; Kartika, Imelda Rahmayunia (Universitas Fort De Kock Bukittinggi, 2022)
Background: One of the government's efforts to reduce learning loss (low learning motivation) in students due to the Covid-19 pandemic is to conduct limited face-to-face learning (PTMT), with the condition that all school equipment has been vaccinated. Especially when the spread of the Covid-19 virus is increasingly massive and easy to attack children. Children's rights must still be given, but still prioritize the health and safety of children. Therefore, the provision of vaccines is not only applied to teaching staff, but must also be given to students, especially school-age children. The purpose of this study was to determine the effect of vaccination on student motivation in one of the SD Negeri Bukittinggi. Methods: This study uses a quasi-experimental method with a one group pre-test-post-test only approach. This study was conducted on 53 elementary school students who participated in vaccination using a questionnaire adapted from Natun (2019). Results: The results showed that there was a significant effect of vaccination on the learning motivation of elementary school students (p.value 0.006). Conclusion: It is hoped that teachers and parents can jointly motivate children to take vaccinations. And through this research, it is expected to add concrete data in the morning for health workers and related communities that vaccination does not reduce the learning motivation of school-age students.